Integrating Zakat, Waqf and Sadaqah: Myint Myat Phu Zin Clinic Model in Myanmar - Sheila Nu Nu Htay; Syed Ahmed Salman; Soe Myint @ Haji Ilyas (Institute for Research and Community Empowerment (LPPM TAZKIA), 2013)
Objective –The main objective of this paper is to present a Myint Myat Phu Zin Clinic Model that integrates three traditional Islamic tools such as waqf, zakat and sadaqah. It is the first clinic in Myanmar which is established based on the combination of these three concepts for Muslims and non-Muslims. Methods – Case study method and interview technique are used to collect the data and to evaluate the operating clinic model and its management.Result–The findings explain how this clinic model is operating from the funding of waqf, zakat and sadaqah and illustrate the operating model from the sources of fund until how they are utilized for the beneficiaries. The clinic is depending on four sources of income, which are the contribution from Muslims and non-Muslims. The types of income received from Muslims are zakat and sadaqah. The income received from non-Muslims is only the charity.Conclusion –It can be concluded that this clinic model can be used as a model in any other non-Muslim countries with minority Muslim population. The clinic is drastically helping patients although the expenditures become higher. Therefore, researchers suggest introducing cash waqf to make sure the clinic is economically stronger.Keywords: Waqf, Zakat, Sadaqah, Health and Clinic